Mapping SS1-3 chemistry teachers’ interest, self-efficacy, and literacy in teaching for creativity using simulation - Nja, Cecilia Obi; Ukwetang, John Okpa; Orim, Richard Ekonesi; Cornelius-Ukpepi, Bernedette; Ndifon, Rita Asu (Frontiers in Education, 2022)
The purpose of this paper was to analyze chemistry teachers’ interest, literacy, self-efficacy team work and creativity on the use of simulation teaching of concepts in chemistry to enhance students’ creativity skills. Descriptive and exploratory quantitative design was used in the study. The study used 150 serving chemistry teachers of Calabar education zone public education. A 29 items questionnaire was employed to gathered data from respondents. Independent t test, regression and a 2 way analysis of variance was used for data analysis. Results showed that obtained indicated high levels of teacher’ interest, literacy, self-efficacy and team work in the utilization of simulation strategy in teaching chemistry concepts. Results of 2 way analysis of indicated that teachers’ age and years of experience influence teachers self-efficacy and team work and creativity. It was recommended among others that serving teachers’ interest in the use simulation be encouraged to support their learners’ instructional activities in a simulated classroom.